IMMUNOLOGICAL FEATURES OF SEPSIS PHENOTYPES AND ENDOTYPES - Mariia B. Potapova; Vitaly V. Zverev; Maxim A. Babaev; Ekaterina A. Bogdanova; Oksana O. Grin; Irina B. Semenova; Ekaterina A. Meremianina; Oxana A. Svitich (Медицинская иммунология, 2019)
AbstractSepsis is a heterogeneous and life-threatening condition caused by a dysregulated immune response to infection. The most severe form of sepsis is septic shock, characterized by arterial hypotension, impaired tissue perfusion, and hypoxia. Despite new findings in antimicrobial and intensive care therapy, the incidence and mortality rates of sepsis remain high, which underscores the relevance of further investigation of its pathogenesis. In recent years, research has shifted from clinical signs to the analysis of immunological and molecular mechanisms, which has led to the identification of  specific phenotypes and endotypes of the disease. Sepsis phenotypes are based on clinical manifestations and biomarkers, while endotypes are defined by molecular mechanisms, including immune gene expression patterns.This article reviews key aspects of the innate and adaptive immune responses in sepsis, including the activation of proinflammatory cytokines, the development of coagulopathies, and disruptions of endothelial integrity and microvascular regulation.Moreover, the importance of mechanisms such as hyperinflammation, the simultaneous development of immunosuppression and functional exhaustion of immunocompetent cells is emphasized. Thus, immunological biomarkers are considered as a promising tool for patient‘s stratification, prognosis prediction and personalized therapy. Current immunodiagnostic methods are also considered in this article, including quantitative analysis of cytokine levels and assessment of innate immune dysfunction markers.Thus, the current understanding of sepsis as an immunologically heterogeneous syndrome enables researchers to expand existing concepts of its pathogenesis. In contrast to the classical concept which is based on a shift from inflammation to immunosuppression, increasing data highlights the simultaneous presence of both processes in the same patient, making it necessary to reconsider existing diagnostic and therapeutic approaches.